Gladys Black letter to Frederick W. Kent and Thomas H. Kent regarding field notes, December 4, 1981 - Black, Gladyset al (1981)
Field notes were contributed by Gladys Black in a letter to Frederick W. Kent and Thomas H. Kent. A letter contributed by Gladys Black to Peter C. Peterson regarding Snowy Owl sightings, December 30, 1981 is included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed/flatbed